Engaging women in countering violent extremism: avoiding instrumentalisation and furthering agency. Issue 1 (2nd January 2017) - Giscard d'Estaing, Sophie
ABSTRACT: Currently, women are on the frontlines of violent extremism, as recruiters, propagators, suicide bombers, and targets, as well as leaders working on de-radicalisation, counter-messaging, and peacebuilding. It is crucial that the international community and governments engage with women in preventing violent extremism, and focus on the gender-related reasons why women become involved as protagonists and supporters of violent extremism. This article examines the limitations of prevention and countering violent extremism programmes and policies in engaging with women, their roles, and gender-sensitivity. Recognising women's agency, diversity in voices and experiences, and knowledge is fundamental to ensuring their rights and sustainable peace. Their full participation at all levels of decision-making in the design and implementation of preventing and countering violent extremism (PVE/CVE) contributes to the effectiveness and sustainability of these efforts.